A Comparative Study of Compressive Effects on the Morphology and Performance of Carbon Paper and Cloth Electrodes in Redox Flow Batteries. Issue 8 (14th June 2022) - Tenny, Kevin M.; Greco, Katharine V.; van der Heijden, Maxime; Pini, Tommaso; Mularczyk, Adrian; Vasile, Alexandru-Petru; Eller, Jens; Forner-Cuenca, Antoni; Chiang, Yet-Ming; Brushett, Fikile R.
Abstract : Compressing porous carbon electrodes is a common approach to improve flow battery performance, but the resulting impact on electrode structure, fluid dynamics, and cell performance is not well understood. Herein, microtomographic imaging, load cell testing, and flow cell diagnostics are employed to characterize how compression‐induced changes impact pressure drop, polarization, and mass‐transfer scaling. Five different compressions are tested, spanning ranges typically used in literature, for AvCarb 1071 cloth (0%, 9%, 20%, 25%, 32%) and Freudenberg H23 paper (0%, 8%, 12%, 17%, 22%). It is found that the two electrode structures have distinct responses to compression, resulting in differing optimal conditions identified for each material; specifically, the Freudenberg H23 exhibits lower combined ohmic, charge‐transfer, and mass‐transport values at 8% compression, resulting in improved electrochemical performance across all compressive values, as compared to the optimal AvCarb 1071 compression (20%). Overall, Freudenberg H23 exhibits a greater sensitivity to compression with peak electrochemical activity correlating with increased permeability, whereas AvCarb 1071 is insensitive to compressive loads but produces lower electrochemical performance. Herein, the trade‐offs of mechanical robustness on fluid‐dynamic and electrochemical performance between the two electrodes are demonstrated by the aforementioned findings, suggesting each could be used for specific operating environments. Abstract : Herein, carbon cloth and paper electrodes are compressed across a range of thicknesses to observe the structural morphologies, fluid dynamics, and electrochemical responses within a redox flow cell. Combined tomography, load cell testing, pressure drop, and electrochemical measurements reveal key mass‐transfer relationships within the electrode structures, compression ratios, and electrolyte flow rates.